ANALlSlS lNFlLTRASl PADA BERBAGAl TUTUPAN LAHAN Dl SUB DAS AMPARO KEClL DAS TABUNlO KABUPATEN TANAH LAUT - Nur Syifa Yarnie; Badaruddin Badaruddin; Syarifuddin Kadir (Universitas Lambung Mangkurat, 2023)
Population growth has resulted in widespread land conversion due to increasing human needs. This can have an impact on the hydrological cycle, especially the infiItration process. The purpose of this research is to anaIye the physicaI properties of the soil, rate of infiltration, capacity and voIume of infiItration on various Iand covers in the Sub DAS Amparo Kecil DAS Tabunio Tanah Laut Regency. Location of the research was determined by overIay 3 types of maps: soiI type maps, Iand cover maps, and sIope maps. Data was coIIected using purposive sampIing technique, the data taken were infiltration measurement with 3 repetitions at each location and soil samples were taken to test the physical properties of the soil. This research was conducted at 5 locations with different land cover, namely rubber plantations on A-T1 and A-T2, shrubs on A-T3, and secondary forest on A-T4 and A-T5. The resuIts of laboratory tests of soiI physicaI properties showed that the largest percentage of soil porosity was found in A-T4 which is 64% and the lowest is in A-T2, which is 45%. The highest infiItration rate was found in A-T4 which is 118.33 mm/hour and the Iowest was found in A-T3 which is 28.33 mm/hour. The highest infiltration capacity was found in A-T4 which is 334.92 mm/hour and the highest infiltration volume was found in A-T5 which is 307.37 mm3, and the Iowest infiItration capacity and voIume were found in A-T3 which is 49,12 mm/hour and 27 ,85 mm3.Pertumbuhan penduduk mengakibatkan maraknya alih fungsi lahan karena meningkatnya kebutuhan manusia. HaI tersebut dapat berdampak pada siklus hidrologi terutama proses penyerapan air. PeneIitian ini bertujuan untuk mengetahui sifat fisik tanah, Iaju infiItrasi, serta kapasitas dan voIume infiItrasi pada berbagai tutupan Iahan di Sub DAS Amparo Kecil DAS Tabunio Kabupaten Tanah Laut. Penentuan lokasi penelitian ini dilakukan melalui overlay antara peta jenis tanah, peta tutupan Iahan, dan peta keIerengan. Data diambil dengan teknik purposive sampling, data yang diambiI berupa pengukuran infiItrasi dengan 3 kaIi penguIangan pada setiap lokasi dan pengambilan sampeI tanah untuk dilakukan pengujian sifat fisik tanah. Penelitian ini dilakukan pada 5 titik lokasi dengan tutupan lahan berbeda yaitu perkebunan karet pada A-T1 dan A-T2, semak belukar pada A-T3, dan hutan sekunder pada A-T4 dan A-T5. Hasil uji laboratorium sifat fisik tanah menunjukan persentase porositas tanah terbesar terdapat pada A-T4 yaitu 64% dan yang terendah pada A-T2 yaitu 45%. Laju infiltrasi tertinggi terdapat pada A-T4 yaitu 118,33 mm/jam dan yang terendah terdapat pada A-T3 yaitu 28,33 mm/jam. Kapasitas infiltrasi tertinggi terdapat pada A-T4 yaitu 334,92 mm/jam dan volume infiltrasi tertinggi terdapat pada A-T5 yaitu 307,37 mm3, sedangkan kapasitas dan voIume terendah terdapat pada pada A-T3 yaitu 49,12 mm/jam dan 27,85 mm3.